The Impact of Using Understanding by Design (UbD) Model on Class 10 Student’s Achievement in Chemistry - Sonam Tshering (International Journal of Chemistry Education Research, 2022)
The purpose of this action research was to examine the impacts of Understanding by Design (UbD) Model on class ten student's achievement in chemistry. The study population comprises students of class 10 of Mendrelgang Central School. A sample of 62 students: 22 boys and 40 girls, was drawn using the purposive sampling technique. The participants were divided into two groups, the control and the experimental group. The pretest-posttest control group experimental design is used for this study. This study focuses on investigating the effectiveness of the Understanding by Design model in improving class ten students' achievement in chemistry. The result shows a non-significant difference between the control and experimental group's mean score on the Academic Achievement of Chemistry Test (AACT) for class ten before applying UbD Model (pre-test),  a significant difference between the control and experimental group's mean score of the Academic Achievement of Chemistry Test (AACT) for class ten after applying UbD Model (post-test) and significant difference between boys and girls mean score of the Academic Achievement of Chemistry Test (AACT) for class ten before applying UbD Model. Keywords: Understanding by Design (UbD) Model, Student's Achievement, Class 10 Students, Achievement in Chemistry